2018
DOI: 10.1098/rspb.2018.1635
|View full text |Cite
|
Sign up to set email alerts
|

An innovative ovipositor for niche exploitation impacts genital coevolution between sexes in a fruit-damaging Drosophila

Abstract: Limited attention has been given to ecological factors influencing the coevolution of male and female genitalia. The innovative ovipositor of Drosophila suzukii, an invading fruit pest, represents an appealing case to document this phenomenon. The serrated saw-like ovipositor is used to pierce the hard skin of ripening fruits that are not used by other fruit flies that prefer soft decaying fruits. Here, we highlight another function of the ovipositor related to its involvement in genital coupling during copula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 32 publications
3
45
0
Order By: Relevance
“…One possible explanation for the limited plasticity of the ovipositor could be the effect of stabilizing selection, which could reduce its range of variation. This limited plasticity is congruent with the limited geographic variation detected and previous evidence on coevolution of the ovipositor with the male genitalia (Muto et al, 2018), expected for a trait under stabilizing selection (Eberhard, 2009;Eberhard et al, 1998). A formal Qst/FSt comparison (Ovaskainen et al, 2011) would nevertheless be necessary to test this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One possible explanation for the limited plasticity of the ovipositor could be the effect of stabilizing selection, which could reduce its range of variation. This limited plasticity is congruent with the limited geographic variation detected and previous evidence on coevolution of the ovipositor with the male genitalia (Muto et al, 2018), expected for a trait under stabilizing selection (Eberhard, 2009;Eberhard et al, 1998). A formal Qst/FSt comparison (Ovaskainen et al, 2011) would nevertheless be necessary to test this hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…This should be tested experimentally by evaluating the relative performance on a variety of substrates, of the cold and hot-generated ovipositors. Other factors like the existence of alternative selective pressures imposed on the ovipositor morphology such as sexual coevolution (Muto et al, 2018) and pleiotropic genetic effects during the ovipositor development (Green et al, 2018) might limit to such morphological adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is also possible that Or85a is only predicted to be a nonfunctional pseudogene from the genomic analyses of D. suzukii due to a premature stop codon. In this case, a shortened sequence for Or85a in D. suzukii might retain functional expression, albeit with a novel ligand spectrum, and thus Or85a acts as a pseudopseudogene, which is a phenomenon that has been previously described in D. melanogaster 53 . However, this has only been documented for an ionotropic glutamate receptor (IR), and the present suggestion would be the first known case of an OR that acts as a pseudo-pseudogene.…”
Section: Discussionmentioning
confidence: 67%
“…Experimental studies imposing different selective regimes have demonstrated that male traits undergo earlier changes within a population relative to females (Cayetano, Maklakov, Brooks, & Bonduriansky, 2011;Wigby & Chapman, 2004), indirectly suggesting a greater influence of selection on males. In contrast, recent studies within populations and between recently diverged species have suggested that novel traits in females may elicit changes in males (Muto et al, 2018;Tanabe & Sota, 2014). However, it remains enigmatic whether any of these processes have played out in any group over long time scales, thereby explaining broad macro-evolutionary patterns of trait diversification.…”
mentioning
confidence: 98%